2019
DOI: 10.1029/2018jg004995
|View full text |Cite
|
Sign up to set email alerts
|

Soil Organic Carbon Stabilization in the Three Subtropical Forests: Importance of Clay and Metal Oxides

Abstract: Field observations show that subtropical forests can accumulate soil organic carbon (SOC) at high rate; however, the key mechanisms of SOC accumulation in subtropical forests remain unclear. Here we selected three typical subtropical forests with soil originated from same parent material under same climate condition in Dinghushan Biosphere Reserve, southern China: coniferous forest, mixed forest, and broadleaved forest with very different rates of SOC accumulation over the last three decades. To quantify the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 87 publications
(129 reference statements)
3
13
0
Order By: Relevance
“…This may be the consequence of basic ions in the muddy soil being washed out, which led to H + rich ions in the soil and more acid being generated by the decay of organic matter. SinceYu et al (2019) suggested that soil pH doesn't play a significant role in the accumulation of SOC, which strongly supports the present study. Soil organic carbon with Oak Forest found a strong positive correlation with the other two forest types which could be result from better nutrient input through litterfall and an increase in regenerating oak trees.…”
supporting
confidence: 91%
“…This may be the consequence of basic ions in the muddy soil being washed out, which led to H + rich ions in the soil and more acid being generated by the decay of organic matter. SinceYu et al (2019) suggested that soil pH doesn't play a significant role in the accumulation of SOC, which strongly supports the present study. Soil organic carbon with Oak Forest found a strong positive correlation with the other two forest types which could be result from better nutrient input through litterfall and an increase in regenerating oak trees.…”
supporting
confidence: 91%
“…Zonal climatic conditions could change soil nutrient flux and soil nutrient allocation by affecting vegetation composition, litter quality, and the exchange of matter and energy between the soil and the environment (Jiang et al, 2019 ). Likewise, under the combined influence of various factors, soil pH and SOC also changed with elevation (Yu et al, 2019 ; Zhu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, nitrapyrin may be more effective in controlling organic carbon transformation in soils with higher SOC and clay content. 42 Apart from these, the inhibitory effects of NI application on soil N transformation and Ncycling related microbial community are likely to impact the microbial processes of SOC decomposition. 12 Following this, Raza et al 8 found that the ability of DCD to reduce CO 2 emissions from calcareous soils in the Loess Plateau was closely associated with its ability to constrain soil nitrification and reduce AOB abundance.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Fisk et al showed that the added nitrapyrin was adsorbed by the soil organic matter, which led to reductions of its degradation rate and volatilization potential. Therefore, nitrapyrin may be more effective in controlling organic carbon transformation in soils with higher SOC and clay content . Apart from these, the inhibitory effects of NI application on soil N transformation and N-cycling related microbial community are likely to impact the microbial processes of SOC decomposition .…”
Section: Discussionmentioning
confidence: 99%